« Up came the leaves » : l’antéposition des groupes prépositionnels (GP) et particules adverbiales comme marqueur de style - Jean ALBRESPIT (E-REA)
The aim of this paper is twofold: (a) to re-examine the different types of locative inversion involving prepositional phrases and adverbial particles with a focus on the syntactic rules that make such constructions possible. Usual explanations in terms of text coherence and emphasis are reassessed and (b) to show that locative inversion is a marker of style. The goal of this study is to show that a change in word order indicates that a change in the narrative structure is taking place and at the same time that the style has changed as well. The phenomenon is particularly salient in fiction for children. The notion of style is thus examined in its relationships with linguistic constructions.